2018
DOI: 10.1016/j.jdsr.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Implant treatment in ultra-aged society

Abstract: SummaryImplant therapy is gaining presence as a prosthodontic treatment option. However, the graying of the population has led to an increase in the number of older adults requiring special consideration in implant treatment because of their systemic health problems. Additionally, with the growth of the elderly population in need of long-term care, a greater number of older adults who have received implant treatment are receiving long-term care, raising various issues that need to be addressed. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…It can be noted that in 2017 approximately one out of six participants reported that they had an implant (14.6%). This can be compared to Japan where only a little more than 1% of 75‐84 year olds had implants in 2011 18 . Another Japanese study from 2018 on patients receiving home‐visit dental care, reported that approximately 3% had received implant therapy 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be noted that in 2017 approximately one out of six participants reported that they had an implant (14.6%). This can be compared to Japan where only a little more than 1% of 75‐84 year olds had implants in 2011 18 . Another Japanese study from 2018 on patients receiving home‐visit dental care, reported that approximately 3% had received implant therapy 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the fact that there is insu cient evidence for actions against implant troubles in visiting dental care is a problem. While position papers by experts [15,16] are beginning to be published, the accumulation of evidence and establishment of guidelines are also necessary. To do this, we need to conduct more surveys on actual conditions in visiting dental care, in order to determine the relationship between individual patients and level of trouble, such as the degree of autonomy of the patient and the level of peri-implantitis [4].…”
Section: Actual State Of Countermeasures For Implant Problemsmentioning
confidence: 99%
“…Replacement of the missing teeth with dental implants is a common treatment modality for restoring the masticatory ability [4,5]. Restoring the posterior edentulous area with implant-supported restorations can not only significantly improve the patient's masticatory function [6], but also relieve the psychological stress by its chewing effect [7]. A patient-centered retrospective study reported that the oral health-related quality of life and overall treatment satisfaction were high in the implant-supported fixed dental restorations [8].…”
Section: Introductionmentioning
confidence: 99%